Clinical experiences of staff and students in transitioning from in-person to blended teaching - Nasseripour, Melanie; Angelova Volponi, Ana; Rajadurai, Susha; Turner, Jonathan; Dahir Hassan, Muna; Bartlett, Anitha; San Diego, Jonathan (Frontiers in Oral Health, 2024)
The present paper describes some of the lessons learned during COVID 19 Pandemic from a study conducted with a group of clinical teachers and undergraduate dental students at the Faculty of Dentistry, Oral & Craniofacial Sciences (FoDOCS) at King's College London about the use of a mix of remote, online and in-person teaching methods which resumed from June 2020. In the narrative research, participants provided accounts of their experiences delivering online clinical workshops and previous experiences delivering face-to-face sessions online, respectively during the pandemic and before the pandemic. We conducted remote interviews with the participants via video conferencing, which were recorded, transcribed, and analysed using thematic analysis. Narrative accounts revealed commonalities organized into seven themes, highlighting some of the challenges faced during the pandemic, as well as insights into how different curricular constraints and concerns can be addressed when various delivery modes are utilized during emergency situations, such as pandemics. In our study, we concluded that students and teachers benefit from dissociating clinical learning from clinical treatment sessions in order to focus on the educational intent and content prior to applying that content chairside with patients. Throughout the course, students and teachers were challenged by a lack of engagement. In addition, it is important to examine the online fatigue highlighted by both students and teachers and identify ways in which time, literacy, and facilitation can be improved to create a kinder, more conducive learning environment. An evidence-based approach should be used to inform this "improvement."During the pandemic, higher education institutions embraced innovative pedagogical approaches which involved technology enhanced learning (TEL). Blended learning (combination of in-person and online) became part of the mainstream teaching and learning as it supports the use of TEL in teaching session activities involving training, presentations, discussion groups both in synchronous and Formatted: Font: (Default) Times New Roman